Quality and sustainability in higher education institutions: key factors - dos Santos Martins, H.; Loureiro, S. M. C.; Amorim, M. (International Journal of Management Cases, 2013)
The main purpose of this paper is to go further in understanding the key factors for quality (e.g., Rusinko, 2005; Yeo, 2009) and sustainability (e.g., Carew and Mitchell 2008, Clarke & Kouri 2009) for industrial engineering and management education in Higher Education Institutions (HEI). Therefore, a systematic literature review was conducted to conceptualize quality and sustainability followed by qualitative research with a sample of professors from selected HEI for validation and refinement of previous studies. The interview protocol included firstly detailed specifications for the selection of professors and the process of contact and invitation for the interview, the request of permission to record the conversation and a brief explanation about the interviewing process. In the interview we used a set of guiding questions regarding quality and sustainability in HEI. The transcribed interviews were analyzed using the WebQDA software. The main key factors identified are: (1) the employability of students and (2) the quality of academic staff and of the facilities. The results also lead to conclude that university professors are not yet truly aware of the importance of marketing tools for a more in-depth dissemination of the work and projects developed in the courses.